Stimulating Catheter as a Tool to Evaluate Peripheral Nerve Function During Hip Rotationplasty. Issue 6 (1st November 2007) - Werdehausen, Robert; Braun, Sebastian; Hermanns, Henning; Krauspe, Rüdiger; Lipfert, Peter; Stevens, Markus F.
Abstract : Objective: Stimulating catheters have been introduced into clinical practice to confirm perineural localization of the catheters. The muscular twitch induced over the catheter may be used to evaluate nerve function intraoperatively. Therefore, the function of the sciatic nerve was evaluated during major cancer surgery of the femur. Case Report: A 7-year-old boy (29 kg) was scheduled for hip rotationplasty for resection of an osteosarcoma of the left femur under general anesthesia and postoperative pain therapy with an epidural stimulating catheter. In hip rotationplasty the femur is resected, the lower limb and foot are rotated 180 degrees and the tibia plateau is attached to the pelvic acetabulum to form a new hip joint. During preparation of the left thigh and the sciatic nerve, motor responses to stimulation of the catheter were preserved, but the stimulation threshold increased. After vascular anastomosis the foot remained cold, therefore ropivacaine was applied epidurally and subsequently a warming of the foot was observed. At the end of the operation, the patient was free of pain, a good capillary pulse of the leg was observed, and the patient was able to move the foot and toes of the rotated leg. Conclusions: The use of epidural stimulating catheters as a tool to monitor nerve function is a novel and simple procedure to monitor nerve function intraoperatively and to enable good postoperative pain control.